Mascotas silvestres en la práctica veterinaria de Guatemala - Lepe López, Manuel Antonio (2018)
Veterinary practitioners of small species are often faced with the challenge of treating wild species patients. This situation requires that the clinicians of animals of these species have special skills and knowledge that allow them to solve cases. To generate information about wild species that are taken to veterinary clinics in Guatemala, an opinion survey was conducted to veterinary practitioners in small animal clinics. A total of 143 professionals participated (1:1 gender ratio). The participants indicated that the rabbit (Oryctolagus cuniculus), the turtle (Trachemys sp and Kinosternon sp), the Australian parakeet (Melopsittacus undulatus), the guinea pig (Cavia porcellus) and the hamster (Mesocricetus auratus) are the most frequent species. In addition, veterinarians noted that 92.3% of patients are received and treated and 5.6% were referred to other clinics. Only 18% knows with certainty the animal species of the wild patients that they treat and 47% declared to know the animal species in most of the cases.